Omega-3 polyunsaturated fatty acids and cardiovascular disease - Yates, Clara M.; Calder, Philip C.; Rainger, G. Ed (2011)
The omega-3 polyunsaturated fatty acids (n-3 PUFAs), docosahexaenoic acid (DHA; 22:6n-3) and eicosapentaenoic acid (EPA; 20:5n-3) (Figure 1) are naturally occurring fatty acids found in high amounts in seafood especially fatty fish (e.g. salmon, herring, sardines, mackerel, tuna). These fatty acids are also found in fish oil supplements. In the 1960s and 1970s it was observed that Greenland Inuits, native Alaskans and the inhabitants of Okinawa, Japan, had a much reduced risk of developing coronary artery disease compared to ‘western’ populations1-4 and that this was associated with a diet rich in n-3 PUFAs. Thus, the ‘cardioprotective’ hypothesis related to n-3 PUFA consumption was engendered. Much research has been carried out in the intervening years on the beneficial effects of consuming n-3 PUFAs. Here we review the data from epidemiological and interventional studies as well as mechanistic studies on the actions of dietary n-3 PUFAs in the cardiovascular system.